An investigation of the anger levels of residents: medical compared with surgical disciplines - Satar, S (BMJ Group, 2005)
Objective: To evaluate medical and surgical residents' anger levels with regard to the department in which they worked, seniority, sex, satisfaction with their work environment, and the number of nightshifts worked per month. The specific situations and persons at whom residents reacted with anger were also investigated. Methods: 116 randomly selected residents staffed in a university hospital (62 medical and 54 surgical residents) were enrolled. The trait anger and anger expression scale was used to find out the personal anger levels of each participant. The participants also clarified the persons and situations that made them angry at work. Results: Trait anger levels were greater in the surgical residents in their first two years when compared with levels of their senior colleagues (p = 0.033). Mean trait anger levels were greater in the residents who were not satisfied with their department (p = 0.004). Anger levels were not found to be related to the number of shifts per month. Male residents had higher levels of anger than female colleagues (p = 0.019). Conclusion: Residents in clinical sciences seem to have the potential to benefit from a screening process in terms of anger and its subcomponents by means of a tool such as the trait anger and anger expression scale during their residency.